Lipid raft-associated β-adducin participates in neutrophil migration - Yang, Chen (Mol Med Rep, 2018)
Previous studies have demonstrated that lipid rafts and β-adducin serve an important role in leukocyte rolling. In the present study the migratory ability and behavior of neutrophils was demonstrated to rely on the integrity of the lipid raft structure. β-adducin was demonstrated to have a critical role in neutrophil migration. Knockdown of β-adducin attenuated the migratory ability of dHL-60 cells and the distribution of β-adducin in lipid raft structures was changed by N-formylmethionyl-leucyl-phenyl-alanine treatment. Furthermore, the findings demonstrated that the tyrosine phosphorylation of β-adducin was required for its relocation. The results of the present study suggested that the lipid raft-associated protein β-adducin may be a novel control point for the excessive infiltration of neutrophils during inflammation.